Dog eat dog [videorecording (DVD)] - Wilder, Matthew (Screenwriter); Cage, Nicolas, 1965-; Dafoe, Willem; Cook, Christopher Matthew; Krause, Louisa, 1986-; Dorsey, Omar J., 1975-; Gallegos, Rey; Dynan, Alexander, 1985-; Bunker, Edward, 1933-2005 (RLJ Entertainment, 2016)
A trio of ex-cons, deep in the underbelly of Los Angeles, are hired for a kidnapping. When the abduction goes awry and gets completely out of control, the cons find themselves on the run, vowing to stay out of prison at all costs.